Kajian Pemulihan Ekonomi Daerah dalam Penanganan Dampak Pandemi Covid-19 di Kota Tanjungpinang Tahun 2021 - Raja Hardiansyah; Eka Kurnia Saputra; Armansyah Armansyah; Dewi Monalisa Putri (Ideas Publishing, 2022)
This research is aqualitative descriptive research that aims to provide policy alternatives for Regional Economic Recovery Budgeting, Labor-Intensive Programs and Social Safety Nets for the Government of Tanjungpinang City in the 2021 planning and budgeting process as an effort to overcome the economic and social impacts on society after the Covid-19 pandemic. The research method used in this research is descriptive method with a qualitative approach and data collection techniques are carried out by interview methods, data analysis is inductive, and the results of qualitative research emphasize meaning rather than generalizations. Based on a study of the Tanjungpinang City RKPD for 2021, it can be formulated as many as 32 programs and 39 activities which can be grouped into, the Regional Economic Recovery Program as many as 21 programs and 25 activities with a budget of Rp20,392,960,733,00, the Labor Intensive Program consists of 5 programs and 5 activities with a budget of Rp50,643,400,000,00, the Social Safety Net Program consists of 6 programs and 9 activities with a budget of Rp34,813,067,000,00.